THE MAIN DIRECTIONS OF DEVELOPMENT OF «ELECTRONIC GOVERNMENT» IN RUSSIA AND THE ESTABLISHMENT OF «PROJECT OFFICES» - Tatiana Anopchenko; Sergey Kirsanov; Vachagan Grigoryan (Вестник Северо-Кавказского федерального университета)
Problems in the development of e-government are primarily that the power of the Internet to increase the availability of authorities of subjects of the Russian Federation are still poorly. Investment in the construction of online representations might be more effective if during the development of the concepts of the sites meets the needs of the citizens.